2015
DOI: 10.1002/14651858.cd011293.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy for asthma

Abstract: Lack of data for important outcomes such as exacerbations and quality of life and use of different unvalidated symptom and medication scores have limited our ability to draw a clinically useful conclusion. Further research using validated scales and important outcomes for patients and decision makers is needed so that SLIT can be properly assessed as clinical treatment for asthma. Very few serious adverse events have been reported, but most studies have included patients with intermittent or mild asthma, so we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 150 publications
0
26
0
3
Order By: Relevance
“…Since then, a number of studies clearly showed that it is effective in allergic rhinitis, although its efficacy in allergic asthma is still debated. In fact, the recent Cochrane review in this topic [111] could not achieve a definitive conclusion. However, in studies that included evaluation of asthma as secondary endpoint it has been shown a significant impact for SLIT on asthma symptoms and on use of medication [112].…”
Section: Sublingual Immunotherapymentioning
confidence: 96%
“…Since then, a number of studies clearly showed that it is effective in allergic rhinitis, although its efficacy in allergic asthma is still debated. In fact, the recent Cochrane review in this topic [111] could not achieve a definitive conclusion. However, in studies that included evaluation of asthma as secondary endpoint it has been shown a significant impact for SLIT on asthma symptoms and on use of medication [112].…”
Section: Sublingual Immunotherapymentioning
confidence: 96%
“…209 A study of SLIT for house dust mites (HDM) in patients with asthma and HDM allergic rhinitis demonstrated a modest reduction of ICS with high dose SLIT. 210 Adverse effects include mild oral and gastrointestinal symptoms.…”
Section: Scitmentioning
confidence: 99%
“…210 Adverse effects include mild oral and gastrointestinal symptoms. 209 Compared to pharmacological and avoidance options, potential benefits of allergen immunotherapy must be weighed against the risk of adverse effects, and the inconvenience and cost of the prolonged course of therapy (Evidence D).…”
Section: Scitmentioning
confidence: 99%
“…Five reviews assessed the benefits of allergen immunotherapy among patients with a primary complaint of allergic asthma 1,[16][17][18][19] Records identified through database searching n = 329* Additional records identified through other sources n = 34…”
Section: Allergic Asthmamentioning
confidence: 99%
“…One review assessed asthma symptom score, medication score and quality of life among patients who received SLIT but did not provide an estimate of overall summary effect owing to methodological heterogeneity. 17 Symptom score: Four reviews reported that participants receiving SCIT or SLIT had significantly improved symptom scores relative to placebo (standardized mean difference [SMD] range -1.02 to -0.59); 1,16,18,19 however, the effect estimates were associated with high heterogeneity (I 2 = 73%-92%) ( Table 2).…”
Section: Allergic Asthmamentioning
confidence: 99%